2018
DOI: 10.1111/andr.12507
|View full text |Cite
|
Sign up to set email alerts
|

The volume of unilaterally undescended testis afterhCGtherapy compared to orchidopexy and combined methods

Abstract: The aim of the study was to compare the effects of human chorionic gonadotropin (hCG) therapy with those of surgical or combined therapy on testicular volume (TV) in boys at different ages with unilateral canalicular undescended testis (UDT). In total, 155 boys aged 1 to 12 years were treated: either surgically (ST), or by 50 IU/kg body weight hCG administration every three days for five weeks (HT), or by a combination of the two. The patients underwent ultrasound examination of TV before the treatment, 9-12 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…19 Using the formula reported by Niedzielski et al, our results were similar, indicating the accuracy and reproducibility of the USG measurement. 20 Kuijper et al reported that the mean testicular volume in 0-year-old to 6-year-old boys increased from 0.27 cc to 0.44 cc in the first 5 months of life, 21 indicating that USG can detect subtle but significant changes in testicular volumes during the infantile period, and our results are consistent with such subtle but significant changes (table 1).…”
Section: Discussionsupporting
confidence: 87%
“…19 Using the formula reported by Niedzielski et al, our results were similar, indicating the accuracy and reproducibility of the USG measurement. 20 Kuijper et al reported that the mean testicular volume in 0-year-old to 6-year-old boys increased from 0.27 cc to 0.44 cc in the first 5 months of life, 21 indicating that USG can detect subtle but significant changes in testicular volumes during the infantile period, and our results are consistent with such subtle but significant changes (table 1).…”
Section: Discussionsupporting
confidence: 87%
“…Precise evaluation of the degree of testicular atrophy determines further treatment in a number of patients. In our opinion, reliable assessment can only be done using TV and TAI calculated on the basis of the ultrasound recordings [ 2 , 25 ]. Thanks to this precise assessment we were able to reveal that the volume of testes submitted to 2SLF-SO increased with advancing age, while the difference in volume between the healthy and undescended testis decreased to only 5% at the age of 7–9 years.…”
Section: Discussionmentioning
confidence: 99%
“…The theoretical basis of hormone treatment for cryptorchidism is that hypothalamic–pituitary–gonadal (HPG) axis hormone deficiency can lead to cryptorchidism, whereas human chorionic gonadotropin (hCG) and gonadotropin-releasing hormone (GnRH) can stimulate the synthesis of testosterone and promote the testicular descent to the scrotum ( 29 , 30 ). Many studies have shown that hCG therapy and luteinizing hormone-releasing hormone (LHRH) or GnRH therapy are more effective in the hormone treatment of cryptorchidism ( 31 , 32 ). The effect of hCG on testicular stromal cells can promote testosterone synthesis.…”
Section: Treatment Of Cryptorchidismmentioning
confidence: 99%